2022
DOI: 10.1002/aisy.202100271
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Soft Robotic Fish for Wireless Underwater Control of Gliding Locomotion

Abstract: Animal locomotion offers valuable references as it is a critical component of survival as animals adapting to a specific environment. Especially, underwater locomotion poses a challenge because water exerts a high antagonistic drag force against the direction of progress. However, marine vertebrates usually use much lower aerobic energy for locomotion than aerial or terrestrial vertebrates due to their unique intermittent gliding locomotion. None of the prior works demonstrate the locomotive strategies of mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…1B ; see the “Fabrication of the HASEL jellyfish robot” section in Materials and Methods). As a feasible improvement in future development, an active buoyance control unit, e.g., using thermally actuated liquid-gas phase transitions ( 3 , 35 , 36 ), can be incorporated into the platform to assist even more agile locomotion and various functions of the robot. For example, the buoyancy could be notably increased when the unit’s volume is enlarged by heating the low–boiling point liquid inside, which can increase the buoyancy and enhance the upward propulsion and transportation of the objects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B ; see the “Fabrication of the HASEL jellyfish robot” section in Materials and Methods). As a feasible improvement in future development, an active buoyance control unit, e.g., using thermally actuated liquid-gas phase transitions ( 3 , 35 , 36 ), can be incorporated into the platform to assist even more agile locomotion and various functions of the robot. For example, the buoyancy could be notably increased when the unit’s volume is enlarged by heating the low–boiling point liquid inside, which can increase the buoyancy and enhance the upward propulsion and transportation of the objects.…”
Section: Resultsmentioning
confidence: 99%
“…One possible solution would be to separate the grippers from the propellers, place them on the bottom, and use all six lappets as propellers to enhance the thrust. Second, practical approaches from other established research fields, such as buoyancy-tunable mechanisms ( 11 , 35 , 36 ) , could be incorporated into our platform for much enhanced loading-carrying capability. For example, after the robot approaches the targeted location efficiently and grasps the objects, inflation of the buoyancy-tunable unit by heating up the low–boiling point liquid inside can notably increase the buoyancy force for the effective upward transportation of real-world trash.…”
Section: Resultsmentioning
confidence: 99%
“…80 In addition, thermo-pneumatic actuation uses the expansion of gas, 81 or a change in the volume of liquid or solid in a confined space under heat input. 106 The phase change happens with liquid evaporating into gas 76,107 or solid melting into liquid, resulting in considerable volume expansion. This phenomenon increases pressure to deflect the flexible walls of the confined space and do external work on the environment.…”
Section: Actuation Principlesmentioning
confidence: 99%
“…This phenomenon increases pressure to deflect the flexible walls of the confined space and do external work on the environment. The actuating flexible structures can be in the form of membranes, 108 inflatable chambers, 76,107 or bellows, 81 where the surrounding walls deflect to create the actuation. Yoon et al 76 reported a phase change soft actuator capable of bi-directional operation by thermoelectric heating and cooling.…”
Section: Actuation Principlesmentioning
confidence: 99%
“…Yoerger et al proposed marine robots capable of tracking the movements of jellyfish and larvae at depths of 200 m. 81 Inspired by marine vertebrates, Lee et al developed a flatfish-like robot that can be controlled by soft thermoelectric pneumatic actuators and can move freely in three dimensions in the water. 82 Small-scale biohybrid robots have been proven to be able to complete locomotion modes such as crawling, rolling, and swimming, but scaling up the biohybrid robots, such as mass fabrication of biohybrid robots beyond the centimeter level, remains challenging. 83 Further research in terms of tissue survival, the interaction of biological interfaces and the control methods of biological tissues are still needed.…”
Section: Multiple Units For Miniature Soft Robotsmentioning
confidence: 99%